Komitmen Kepemimpinan BAZNAS dalam Mengoptimalkan Potensi Zakat dan Memperkuat Ekonomi Masyarakat - Samsi Samsi; Yitno Puguh Martomo; Erwinda Sam Anafih (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
This study employs a qualitative case study approach to examine the leadership commitment of the National Zakat Amil Agency (BAZNAS) in optimizing zakat potential and empowering the community economy in Karanganyar Regency. Data were collected through observations, document analysis, and in-depth interviews with key stakeholders, including BAZNAS leaders and managers. Data analysis was conducted using triangulation to ensure the validity and reliability of the findings. The results reveal that effective zakat management, driven by program innovation and supported by local government initiatives, significantly contributes to economic empowerment. Nonetheless, challenges such as low public participation, limited digital integration, and disparities in zakat distribution remain. Overcoming these issues necessitates strengthening governance, improving public awareness, integrating technological solutions, and implementing data-driven distribution strategies with oversight from independent supervisors. In conclusion, zakat possesses substantial potential for economic empowerment when managed with a firm commitment aligned with Islamic principles. The unwavering dedication of BAZNAS leadership can transform zakat management and distribution into a catalyst for economic growth, enhanced community welfare, and sustainable poverty reduction in Karanganyar Regency.